2022
DOI: 10.3389/fnut.2022.808355
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Dietary Patterns and Associations With IVF Outcomes: An Ongoing Prospective Cohort Study

Abstract: There is a lack of research on preconception diet and reproductive outcomes conducted in the Chinese population using individual assessment. Between April 2017 and April 2020, 2,796 couples undergoing in vitro fertilization treatment were recruited in this ongoing prospective cohort, and 1,500 eligible couples were included in the final analysis. A validated semi-quantitative food frequency questionnaire was used to evaluate the maternal preconception diet. Other lifestyle factors, including smoking status, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…Fatty meals can have acute adverse effects on oocyte mitochondria 15 , and high-fat diets are detrimental to male fertility 16 . A prospective study concluded that ve Chinese food patterns, and the western food style "Puffed food-Candy-Bakery" were related to a lower likelihood of achieving biochemical pregnancy 17 . A primate study involving a short-term high-fat western-style diet before IVF treatment demonstrated that high-fat diet reduces blastocyst numbers, dysregulates RNA binding and mitochondrial function 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Fatty meals can have acute adverse effects on oocyte mitochondria 15 , and high-fat diets are detrimental to male fertility 16 . A prospective study concluded that ve Chinese food patterns, and the western food style "Puffed food-Candy-Bakery" were related to a lower likelihood of achieving biochemical pregnancy 17 . A primate study involving a short-term high-fat western-style diet before IVF treatment demonstrated that high-fat diet reduces blastocyst numbers, dysregulates RNA binding and mitochondrial function 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a prospective study found that certain Chinese food patterns and a Western food style involving “Puffed food-Candy-Bakery” were associated with a lower likelihood of achieving biochemical pregnancy. 17 Additionally, a primate study showed that a short-term high-fat Western-style diet before IVF treatment led to a reduction in blastocyst numbers and dysregulation of RNA binding and mitochondrial function. 18 Consumption of beverages with high sugar content has also been linked to a lower number of total, mature, and fertilized oocytes, as well as a lower number of top-quality embryos after ovarian stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…As described in previous studies [ 12 ], the IVF procedure generally includes four stages: controlled ovarian stimulation (COS), oocyte pick-up (OPU), ET, and pregnancy test ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 hours, the number of oocytes with two pronuclei was determined by embryologists. The cleavage embryo quality was assessed using the Peter system: (1) embryos with more than three cells and anucleate fragmentation <50% were identified as having transferable quality; (2) embryos with 6–10 cells and anucleate fragmentation <20% were considered as high-quality embryos [ 12 ]. Blastocyst formation rate was defined as the number of blastocysts formed divided by the total number of embryos continuously cultured to the blastocyst stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation